A Reduced Switch Count Dual Output Single Phase Inverter (International Journal of Engineering and Computer Science, 2014)
Dual-output three-switch inverter topology is proposed in this paper. To supplying two single-phase ac loads independently with one inverter. Using reduced switch count topology which introduced in three phase converter. This configuration required less no of devices and provide dual output compared to conventional inverters. Which results in reduction in cost, size and  switching losses. The proposed topology is introduced with its gate circuit for switching schemes is elaborated. Simulation model of proposed inverter is developed. Its output waveforms are analyzed. Total harmonic distortion and  performances are compared with different  PWM techniques.